Are prisons safe? Death due to depression while in custody: a case report - Naik, Rupeshkumar; Shaha, Kusa Kumar; Chaudhari, Vinod A. (International Journal of Research in Medical Sciences, 2016)
Prisoners are not born but made. Custodial deaths were becoming crunch to the mistreated police control for so many decades. A 32-year-old male was found dead inside prison because of depression that he was prisoned. On examination, there was ligature mark over neck that was suicidal in nature. Proper care of the prisoners, motivation inside the prison, maintaining surprise visits by higher officials, and closed monitoring by CCTV may prevent these type of suicidal behaviours inside the prison. The present case gives the idea for the police personnel to motivate and monitor the prisoners to prevent suicidal behaviour.